THREE-DIMENSIONAL ASPECTS OF THE MAIN CHARACTER IN DELIA OWENS' WHERE THE CRAWDADS SING - Wahyuni Khotimah; Bunyamin Faisal Syarifudin; Agry Pramita (CALL, 2023)
Egri's three-dimensional theory (1923) was employed to examine the multifaceted aspects of Catherine Danielle Clark, the main character in Delia Owens' novel "Where the Crawdads Sing." This qualitative study utilized a narrative approach to gather and analyze data through inductive and deductive techniques. The findings revealed several three-dimensional aspects of Catherine Danielle Clark. Physically, she possessed beauty, long black hair, and a well-proportioned body with a deep-tanned complexion, which improved as she matured. Socially, she hailed from a lower-class American family, held various jobs as a seafood seller, book writer, and poet, and experienced discrimination and singledom. Her hobbies included reading books and collecting organisms from the marsh. Psychologically, she exhibited introversion, insecurity, sensitivity, irritability, selfishness, anxiety, and a reluctance to forgive. However, she also displayed independence, optimism, and a determined fighting spirit for survival, showcasing remarkable talent in painting and writing. Overall, the study found that the psychological dimension was more pronounced than the physiological and social dimensions. Keywords: main character, physiological dimension, psychological dimension, sociological dimension, three-dimensional aspects